Storytelling as a persuasion strategy in the purchase decision of colombian consumer - Arango Lozano, Carlos Andrés; Peñalosa Otero, Mónica Eugenia; Flores Rueda, Isabel Cristina; Sánchez Macías, Armando (Ingeniería Solidaria, 2025)
This article is the result of research developed by the Communication-Culture-Mediation Group of the Faculty of Social Sciences and the Administration and Management of Organizations AdGeo Group of the Jorge Tadeo Lozano University of Bogotá in 2025.Methods: The study collected in-situ and real-time data, yielding several findings based on 264 surveys conducted with various sales agents. This allowed for an understanding of sales advisors’ perceptions of storytelling, not only as a communication technique but also as a sales strategy.Results: The research presents the findings of a survey conducted with technology salespeople, aimed at evaluating storytelling as an effective technique for engaging consumers in retail settings. The study focused on understanding the salespeople’s perceptions of the usefulness of storytelling in creating emotional connections with customers, and how this strategy can influence purchasing decisions.Conclusions: The study revealed that most salespeople recognize the importance of storytelling as a tool for engaging consumers. Ultimately, this research supports the idea that storytelling is a valuable technique that can play a significant role in persuasive consumer engagement.Originality: The use of storytelling as a persuasive sales strategy by Colombian companies has not been previously addressed, making this article a key contribution to understanding the topic.Limitations: The article also presents various perspectives on the limitations of using storytelling in commercial strategies in Colombia.
Keywords: Storytelling; Sale; Shopping experience